2024
DOI: 10.1021/acs.nanolett.4c01505
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Molecular Interaction of 3D Plasmonic Nanoporous Gold Alloys by Electronic Modulation for Sensitive Molecular Detection

Ju A. La,
Hyunjoo Lee,
Dongchoul Kim
et al.

Abstract: Three-dimensional gold and its alloyed nanoporous structures possess high surface areas and strong local electric fields, rendering them ideal substrates for plasmonic molecular detection. Despite enhancing plasmonic properties and altering molecular interactions, the effect of alloy composition on molecular detection capability has not yet been explored. Here, we report molecular interactions between nanoporous gold alloys and charged molecules by controlling the alloy composition. We demonstrate enhanced ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Recently, the development of porous three-dimensional (3D) substrates has received special attention for efficient SERS detection because of their tunable LSPR properties ranging from ultraviolet (UV) to near-infrared (NIR), high surface area, and strong confinement of electromagnetic (EM) field strength within the pores, which provide optimum sites to interact with the analyte molecules. , Specifically, porous Ag- or Au-containing nanometric pores have been demonstrated to exhibit remarkably enhanced SERS activity for a variety of analyte molecules. For instance, Lim et al showed that mesoporous Ag films exhibited greatly enhanced molecular interaction, and a SERS enhancement factor (EF) on the order of 10 7 to 10 8 was achieved. Also, La and co-workers, have recently demonstrated that the SERS substrate based on nanoporous Au alloys showed a SERS EF up to 10-times greater than that of the monolayer Au NPs and exhibited superior sensitivity down to 1 fM concentrations of analyte molecules. Such nanoporous structures have been prepared through different physical and chemical routes such as chemical synthesis and self-assembly, Langmuir–Blodgett, electron beam lithography, chemical dealloying, electrochemistry, , treatment of oxygen plasma of thermally deposited films, and dewetting of metallic films to create a porous 3D framework.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of porous three-dimensional (3D) substrates has received special attention for efficient SERS detection because of their tunable LSPR properties ranging from ultraviolet (UV) to near-infrared (NIR), high surface area, and strong confinement of electromagnetic (EM) field strength within the pores, which provide optimum sites to interact with the analyte molecules. , Specifically, porous Ag- or Au-containing nanometric pores have been demonstrated to exhibit remarkably enhanced SERS activity for a variety of analyte molecules. For instance, Lim et al showed that mesoporous Ag films exhibited greatly enhanced molecular interaction, and a SERS enhancement factor (EF) on the order of 10 7 to 10 8 was achieved. Also, La and co-workers, have recently demonstrated that the SERS substrate based on nanoporous Au alloys showed a SERS EF up to 10-times greater than that of the monolayer Au NPs and exhibited superior sensitivity down to 1 fM concentrations of analyte molecules. Such nanoporous structures have been prepared through different physical and chemical routes such as chemical synthesis and self-assembly, Langmuir–Blodgett, electron beam lithography, chemical dealloying, electrochemistry, , treatment of oxygen plasma of thermally deposited films, and dewetting of metallic films to create a porous 3D framework.…”
Section: Introductionmentioning
confidence: 99%